Augmented Reality Learning Media for Student Engagement in Literacy Classrooms: Media Pembelajaran Augmented Reality untuk Keterlibatan Siswa dalam Pembelajaran Literasi - Jumriani; Syatriana, Eny; Mukhlis (Indonesian Journal of Innovation Studies, 2025)
Background: Literacy learning in elementary schools frequently relies on conventional approaches that limit student participation and engagement. Specific background: Initial observations showed students’ passive responses, low motivation, and limited exposure to digital media in literacy activities. Knowledge gap: Existing studies have not provided development results of interactive Augmented Reality media aligned with early grade literacy needs. Aims: This study aimed to develop Augmented Reality-based learning media and determine its validity, practicality, and ability to foster student engagement in literacy learning. Results: Using the Four-D development model, expert validation indicated very high feasibility, teacher and student responses demonstrated strong usability, and classroom implementation showed high levels of affective, cognitive, behavioral, and interactive engagement. Novelty: The media integrates visual–audio literacy content and real-time interaction tailored for second-grade learners. Implications: Findings suggest the media can serve as an innovative classroom resource and may be expanded for broader subjects, grade levels, and digital learning environments. Highlights Media demonstrated strong validity and practicality based on expert and user evaluation. Classroom implementation showed high student engagement across multiple engagement dimensions. Interactive visual–audio features supported more active literacy learning experiences. Keywords Augmented Reality, Learning Media, Student Engagement, Literacy Education, Elementary School